Yoga Jalan Merealisasikan Keseimbangan Pikiran dan Kesehatan Tubuh - Komang Heriyanti; Ni Made Evi Kurnia Dewi (Jurnal Yoga dan Kesehatan, 2021)
Yoga is no stranger to human life today. Yoga combines mind, body, and spirit into one integrated and balanced unity. Someone who does yoga seriously will get a healthy body and mind balance. Yoga is not just a movement or posture. Yoga guides a person to control the mind. Therefore yoga seeks to unite the activities of the body with the mind. In this case yoga as a way to self-discipline. Practicing yoga postures is very effective in curing various diseases. But if we are only interested in practicing yoga postures with the primary goal of maintaining a healthy body and not having the goal of healing the mind and emotions, then our confused minds are not in accordance with the condition of the body. Yoga is used as an ability to control emotions or manage emotions that are in themselves properly. When someone is able to exercise control or self-discipline, he will realize devotion to God. The goal of yoga is self-realization that will illuminate and enhance the mind and character of a Yogi. This is a spiritual achievement that is able to make humans discover the higher truths that are within themselves. To understand and understand our hidden selves, there must be a perfection in the conscious mind, so that the deeper layers of the mind can be directed at the level of consciousness.